Transforming the police - Mastrofski, Stephen D. (Journal of research in crime and delinquency, 1993)
The article reviews several books including "Problem-Oriented Policing," by Herman Goldstein, "Policing Domestic Violence: Experiments and Dilemmas," by Lawrence W. Sherman and "Above the Law: Police and the Excessive Use of Force," by Jerome H. Skolnick and James J. Fyfe